Level of urea in high grain diets: finishing steer performance - Milton, C.T.; Brandt, Robert T., Jr. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Eighty-eight medium-framed crossbred steers (731 lb) were used to identify the optimal level of urea in finishing diets for growth and carcass traits. Diets contained no urea or .5, 1.0, or 1.5% urea (dry matter basis) and no other supplemental protein. Feed efficiency and gain were improved substantially by the first increment of urea (.5%), with little or no improvement from subsequent urea additions. Pooled across level, urea improved feed efficiency by 5.6% and gain by 8.9%, whereas dry matter intake declined 3.3% compared to controls. Regression analysis indicated that the optimal level of urea for gain and feed efficiency was .91% of dietary dry matter. Dressing percentage and hot carcass weight responded quadratically, being higher for steers receiving .5 or 1.0% urea. Fat thickness, yield grade, and KPH fat increased linearly with level of urea. Percentage choice carcasses tended to increase, although no differences in marbling score were observed with increased urea. Because of increased carcass weight and finish, with no increase in loineye area, these data suggest that adding urea increased energy utilization (diet digestibility) rather than metabolizable protein supply to the small intestine.
Keywords: Beef; Finishing steers; Urea; Performance; Metabolizable protein